Low carryover risk of corn and soybean herbicides across soil management practices and environments. (8th February 2022) - Grint, Kolby R.; Proctor, Christopher; DeWerff, Ryan; Smith, Daniel H.; Arneson, Nicholas J.; Arriaga, Francisco; Stoltenberg, David; Werle, Rodrigo
Abstract: Herbicides with soil-residual activity have the potential for carryover into subsequent crops, resulting in injury to sensitive crops and limiting productivity if severe. The increased use of soil-residual herbicides in the United States for management of troublesome weeds in corn- and soybean-cropping systems has potential to result in more cases of carryover. Soil management practices have different effects on the soil environment, potentially influencing herbicide degradation and likelihood of carryover. Field experiments were conducted at three sites in 2019 and 2020 to determine the effects of corn (clopyralid and mesotrione) and soybean (fomesafen and imazethapyr) herbicides applied in the fall at reduced rates (25% and 50% of labeled rates) and three soil management practices (tillage, no-tillage, and a fall-established cereal rye cover crop) on subsequent growth and productivity of the cereal rye cover crop and the soybean and corn crops, respectively. Most response variables (cereal rye biomass and crop canopy cover at cover crop termination in the spring, early-season crop stand and herbicide injury ratings, and crop yield) were not affected by herbicide carryover. Corn yield was lower when soil was managed with a cereal rye cover crop compared with tillage at all three sites, while yield was lower for no-till compared with tillage at two sites. Soybean yield was lower when managed with a cereal rye cover crop compared with tillage and no-till at one site. Findings from this research indicate a low carryover risk for these herbicides across site-years when label rotational restrictions are followed and environmental conditions favorable for herbicide degradation exist, regardless of soil management practice on silt loam or silty clay loam soil types in the U.S. Midwest region.